A brief discussion on the development and research of original interactive children's picture books in China / Li Yang, Mastura Mohd Jari and Dai Yongli - Li, Yang; Mohd Jari, Mastura; Dai, Yongli (Faculty of Art and Design, 2023)
With the development of global research on child education, the benefits of reading for children's cognitive development have been widely recognized. Children's picture books serve as important vehicles for children to understand the world around them, establish values, and develop life beliefs. They can also be powerful tools in strengthening parent-child relationships. Currently, an increasing variety of children's picture books are emerging in the public eye. In the children's market in China, there is strong inclusivity toward picture books from different countries, cultures, and artistic styles. Chinese child readers and parents have shown a strong interest in and acceptance of diverse picture book content. This inclusivity provides children with a wider range of reading choices and enriches their learning experiences. In order to better stimulate children's interest in reading and assist parents without parenting or educational experience, it is essential to provide them with better guidance and confidence during parent-child reading sessions. Therefore, in the design process of children's picture books, there are several aspects that designers need to consider comprehensively. Firstly, there should be a clear understanding of the psychological needs of children at different age stages. Secondly, careful consideration should be given to the visual pairing of illustrations and text, visual colour schemes, interactivity, and educational value, as well as the quality and safety aspects of the picture book. The process of reading together with parents and young children is not only a journey for children to understand the world but also a process for parents to understand the world of their children. It is a growth experience for both children and parents, providing them with high-quality bonding time and valuable companionship throughout their lives. Research on children's picture books has been initiated earlier and achieved significant accomplishments in developed countries abroad. Countries such as the United States, the United Kingdom, and Japan have made significant contributions to the development of children's literature through active exploration and innovation in the research and publishing of children's picture books. They pay attention to children's developmental needs and psychological growth, emphasising the quality of content, artistic expression, and educational value. They have set benchmarks in the global children's picture book market and have had a profound impact on the creation and research of children's picture books in other countries. Compared to other countries, China had a relatively late start in the field of children's picture books. However, over the past few decades, the children's picture book market in China has experienced rapid development and transformation. With the growth of the market and the support of policies, there has been continuous progress in content creation, publishing quality, and artistic expression of children's picture books. With increasing attention and support, the creation and research of children's picture books in China are bound to further develop and expand. This article first expounds on the research background and current situation of children's picture books, laying a practical foundation for the purpose and significance of the study. It explores the concept of interactive children's picture books and investigates the interactive forms of excellent children's picture books from abroad. It also examines the direction and forms of interactive design in original children's picture books in China, aiming to establish a new connection between children and picture books. This will better cater to children's curiosity, activity, and engagement needs, and provide a more diverse, interesting, and personalised reading experience.